Meta-analysis and systematic review of the association between adverse childhood events and irritable bowel syndrome. (August 2022) - Joshee, Shreeya; Lim, Lauren; Wybrecht, Alexis; Berriesford, Riley; Riddle, Mark
Irritable bowel syndrome (IBS) is a disorder of gut–brain interaction characterized by abdominal pain, bowel habits alterations, constipation, and/or diarrhea. Adverse childhood experiences (ACEs) are events such as abuse and mental illness causing childhood trauma. Studies report higher prevalence of ACEs in patients with IBS with varied effect consistency and association strength. A systematic review and meta-analysis were conducted to evaluate current literature, assess heterogeneity and research gaps in this relationship. A search across PubMed, Embase, PsycINFO, and Google Scholar with keywords ('childhood adversity' OR 'childhood trauma' OR 'adverse childhood events') AND ('irritable colon' OR 'irritable bowel syndrome') yielded 106 studies. A restricted maximum likelihood model of 15 chosen studies with 272, 686 participants found the association between ACEs and IBS to be uncertain given the considerable heterogeneity (I 2 =93.58%, p<0.001). Objective reporting methods for ACE and IBS, study size, and study quality explained some heterogeneity. Twelve studies showed publication bias (Egger's test, p<0.001), which further weakened interpretation. Gender-stratified subanalysis of three studies found ACEs associated with IBS in females (pOR=2.20, 95% CI (1.13 to 4.29), I 2 =66.90%) with substantial heterogeneity, but no association in males (pOR=1.30, 95% CI (0.62 to 2.78)). This meta-analysis explores the current literature to understand the biopsychosocial perspective of IBS and ACEs' role as risk factors. However, the risk of publication and design/study quality biases substantiates the need for further research. If an association is confirmed, further mechanistic research and development of targeted psychological therapies may be warranted.